Pengaruh Luas Tanah, Modal,Tenaga Kerja, dan Teknologi dalam Meningkatkan Pendapatan Petani Hortikultura di Tinjau dari Produksi Islam: Studi pada Usaha Tani Cabai di Desa Tirta Mulya Kecamatan Airmanjunto Muko Muko - Erli Sefionita; Eka Sriwahyuni; Khozin Zaki (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine how much land area, capital, labor, and technology influence in increasing the income of chili farming in Tirta Mulya Village, Air Manjunto District, to find out the Islamic production view on production factors in increasing the income of chili farmers. The research method used is a quantitative method with primary data collection techniques through questionnaires distributed to 30 chili farmer respondents selected through proportional area random sampling techniques, the data obtained were analyzed using multiple linear analysis techniques with the help of the SPSS version 21 application. The results of the hypothesis testing study using the t test showed that the four independent variables studied were proven to be significant, land area and technology had no effect, capital and labor had a partial effect on the dependent variable, namely farmer income. Through the F test, there is a simultaneous influence between land area, capital, labor, and technology as seen from the F_count 10.468 > 2.76 F_table and a significant value of 0.000 < 0.05, then Ha is accepted, the large influence is seen from the results of the determination coefficient test R^2 of 0.626 or 62.6% while the remaining 38.4% is explained by other factors originating from outside the variables studied. In Islamic production, the production factors used are not only seeking profit but are oriented towards worship so that whatever goods a person produces will emphasize ethics in production.